2015
DOI: 10.1002/gepi.21904
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Smoking Status and Intensity on Discovery of Blood Pressure Loci Through Gene‐Smoking Interactions

Abstract: Background Genetic variation accounts for approximately 30% of blood pressure (BP) variability but most of that variability hasn't been attributed to specific variants. Interactions between genes and BP-associated factors may explain some ‘missing heritability.’ Cigarette smoking increases BP after short-term exposure and decreases BP with longer exposure. Gene-smoking interactions have discovered novel BP loci, but the contribution of smoking status and intensity to gene discovery is unknown. Methods We ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…For example, the SASH1 gene has been associated with thyroid function 26 and suggestively associated with responses to rate control therapy among patients with atrial fibrillation 27 . A more recent study indicated that the SASH1 gene may interact with smoking on SBP 28 . While the role of LOC105369882 in BP is unclear, another gene at this locus, CEP290 , is potentially relevant to BP regulation 29 , with mutations of this gene shown to associate with many disease phenotypes characterized by renal impairment 30, 31 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the SASH1 gene has been associated with thyroid function 26 and suggestively associated with responses to rate control therapy among patients with atrial fibrillation 27 . A more recent study indicated that the SASH1 gene may interact with smoking on SBP 28 . While the role of LOC105369882 in BP is unclear, another gene at this locus, CEP290 , is potentially relevant to BP regulation 29 , with mutations of this gene shown to associate with many disease phenotypes characterized by renal impairment 30, 31 .…”
Section: Discussionmentioning
confidence: 99%
“…BP is known to be modulated by a variety of lifestyle factors, such as diet [21], exercise [22], and smoking [23], as well as other factors such as age [24, 25] and obesity [26]. In GWAS for HTN-related phenotypes, significant GxE interactions have been identified with alcohol consumption [27], body mass index (BMI) [28], smoking [29, 30], education levels [31], and sodium intake [46] which are all modifiable through lifestyle changes. These findings suggest that further investigation into GxE interaction may identify causal genetic loci that contribute to missing heritability [33].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study using a systems biology approach revealed that cigarette smoke induced a concentration-dependent (direct and indirect) biological mechanism that promotes monocyte-endothelial cell adhesion (Poussin et al, 2015). Hence, the influence of smoking intensity on the detection of gene-smoking interaction was previously reported in a study of gene-smoking interaction for blood pressure in the Framingham Heart Study (Basson et al, 2015). They found different associated loci in the light smoker and the heavy smoker groups (>10 cigarettes per day).…”
Section: Discussionmentioning
confidence: 89%